2020
DOI: 10.3390/microorganisms8060945
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Carboxylic Acids to Alcohols: Characterization of Thermoanaerobacter Strain AK152 and 1-Propanol Production via Propionate Reduction

Abstract: Thermoanaerobacter strains have recently gained interest because of their ability to convert short chain fatty acids to alcohols using actively growing cells. Thermoanaerobacter thermohydrosulfuricus strain AK152 was physiologically investigated for its ethanol and other alcohol formation. The temperature and pH optimum of the strain was 70 °C and pH 7.0 and the strain degraded a variety of compounds present in lignocellulosic biomass like monosaccharides, disaccharides, and starch. The strain is highly ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…strain X514, T. brockii ssp. Finnii and T. pseudethanolicus [104][105][106]. AdhE is the bifunctional enzyme including alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) activities, the deletion of which would reduce the ethanol yield by ~95% [107].…”
Section: Ethanol Productionmentioning
confidence: 99%
“…strain X514, T. brockii ssp. Finnii and T. pseudethanolicus [104][105][106]. AdhE is the bifunctional enzyme including alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) activities, the deletion of which would reduce the ethanol yield by ~95% [107].…”
Section: Ethanol Productionmentioning
confidence: 99%
“…Recent investigations have shown that bacteria within the genera of Thermoanaerobacter and Caldanaerobacter can dispose their electrons produced during glucose (and other sugars) oxidations not only to pyruvate to produce ethanol or lactate but may also use other electron acceptors like fatty acids which are converted to their corresponding alcohols [47][48][49]. This was tested for strain AK15 by cultivating the strain on glucose only and on glucose in the presence of butyrate.…”
Section: Conversion Of Fatty Acids To Alcoholsmentioning
confidence: 99%
“…No lactate and hydrogen were observed as end products at end of fermentation in the presence of butyrate This was also investigated for other volatile fatty acids, like propionate, branched chain fatty acids and pentanol, with similar results of the conversion of the fatty acid to their corresponding alcohol (results not shown). Thermoanerobacter pseudethanolicus has recently been shown to convert fatty acids to alcohols, during sugar degradation [25,48] as well as Thermoanerobacter thermohydrosulfuricus, strain AK152 [49]. Production of high carbon alcohols from complex biomass by adding cheap volatile fatty acids to the fermentation broth of the hydrolysates is indeed a new way of biofuel production that may be of great importance in the near future.…”
Section: Conversion Of Fatty Acids To Alcoholsmentioning
confidence: 99%
“…Increased propionate concentrations resulted in increased formation of propanol in all cases. Recently, our research group has shown the capacity of Thermoanaerobacter species to convert fatty acids to their corresponding alcohols [20,27,28] under specific conditions. Instead of dispersing reducing equivalents to pyruvate and produce only ethanol (or lactate), these bacteria used the electrons produced to reduce fatty acids to alcohols.…”
Section: Kinetic Experiments On Glucose and Propionatementioning
confidence: 99%